PENGARUH MODEL PEMBELAJARAN RADEC BERBANTUAN MEDIA CORELDRAW TERHADAP KEMAMPUAN MENULIS POSTERPADA SISWA KELAS XI SMA TAMAN SISWASUKADAMAI T.A 2025/2026 - Silvia Rani Putri Adam; Wan Nurul Atikah Nasution (STKIP Pesisir Selatan, 2026)
This study aims to determine the effect of the RADEC learning model assisted by CorelDraw media on the ability to write poster texts of class XI students of SMA Taman Siswa Sukadamai in the academic year 2025/2026. The problem in this study is the low ability of students in writing Poster texts, especially in understanding the structure of Poster Texts, Content and messages of poster texts, language and sentences. The type of research used is quantitative with an experimental method using the Pottest Only Control Group Design design. The research instrument was a poster text writing ability test. The results showed that the ability to write poster texts in the experimental class was better than the control class, the average value of the control class was 66.42 with a good category, while the experimental class got an average value of 79.28 with a good category. Based on the results of the hypothesis test using the t-test, it was obtained that t count > t table, namely 5.59 > 1.70, so the null hypothesis (Ho) that there is no significant influence is rejected and the alternative hypothesis (Ha) that there is a significant influence of the use of Coreldraw media on the ability to write poster texts in class XI students of SMA Taman Siswa Sukadamai in the 2025/2026 Academic Year is accepted.